Screening for 22q11.2 deletion syndrome by two non-invasive prenatal testing methodologies: A case with discordant results - Liang-Ming Lo; Chii-Shinn Shiau; Kuang-Chao Chen; S.W.S. Shaw; Peter Benn (Elsevier, 2019)
Objective: Non-invasive prenatal testing (NIPT) through the analysis of cell-free DNA in maternal plasma has bee expanded to include clinically-relevant microdeletions such as the 22q11.2 deletion syndrome (22q11.2DS). Case report: We present a pregnancy where the fetus was affected with 22q11.2DS based on chromosome microarray analysis. Discordant results were obtained through two different NIPT methodologies. The pregnancy was identified as high risk by a SNP-based approach but low risk using a genome-wide counting methodology. A review of the technical methods used for these tests provides insight into why they may provide conflicting results and emphasizes the importance of chromosome microarray studies for diagnostic confirmation and defining the deletion. Conclusion: Currently available NIPT for 22q11.2DS use different technologies that are not equivalent. The genome-wide counting methodology has the potential to detect deletions outside the critical 22q11.2 A-D region but current data suggests it may have a lower sensitivity for deletions within the critical region. Keywords: Screening, Prenatal, Non-invasive testing, 22q11.2 deletion syndrome